2018
DOI: 10.1371/journal.pone.0207090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pepsin and pepstatin on reflux tonsil hypertrophy in vitro

Abstract: There is evidence that pepsin can aggravate tonsil hypertrophy. Pepstatin is a potent inhibitor of pepsin activity and could protect patients against reflux tonsil hypertrophy by inhibiting pepsin. We examined the effects of pepstatin on the development of tonsil hypertrophy to investigate pepsin’s role in the pathogenesis of tonsil lesions. We investigated whether pepstatin suppresses pepsin-mediated lymphocyte proliferation in tonsil hypertrophy. Forty-nine children with tonsil hypertrophy and twenty-two adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…25 An in vitro study concluded that pepsin likely aggravates tonsil hypertrophy in the context of GERD, although there is no direct evidence of this association. 26 Further research is required to determine the strength and cause of the GERD association with revision surgery risk. Recurrent or chronic tonsillitis was the most common diagnosis prompting revision surgery in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…25 An in vitro study concluded that pepsin likely aggravates tonsil hypertrophy in the context of GERD, although there is no direct evidence of this association. 26 Further research is required to determine the strength and cause of the GERD association with revision surgery risk. Recurrent or chronic tonsillitis was the most common diagnosis prompting revision surgery in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pepstatin is well known to be an inhibitor of aspartic proteinases such as pepsin, cathepsins D and E [ 55 ]. Kim observed that pepsin from extraesophageal reflux aggravates tonsil hypertrophy and pepstatin exerts a protective effect by inhibiting pepsin activity [ 56 ]. Our results showed that IL-8 level was reduced when pepsin was inhibited by pepstatin; this coincided with significant upregulation of epithelial markers and downregulation of mesenchymal markers.…”
Section: Discussionmentioning
confidence: 99%
“…Pepsin not only damages the laryngopharyngeal mucosa but also induces chronic inflammation of the surrounding tissues to cause vocal fold polyp [37], tonsillar hypertrophy [38,39], otitis media [40], recurrent respiratory papillomatosis [22,41], laryngopharyngeal tumors [34,36] and other diseases.…”
Section: Pepsinmentioning
confidence: 99%